Carrot Cake - Wood, Alix; Owen, Ruth; Sachner, Mark J (Minneapolis, MN : Ruby Tuesday Books, 2024)
"Discover how to grow a crop of delicious carrots and turn them into homemade carrot cake" --back cover.
Includes bibliographical references and index.
Keywords: Carrots -- Juvenile literature; Gardening -- Juvenile literature; Carrot cake -- Juvenile literature; Cooking (Carrots) -- Juvenile literature